Belt and road initiative and healthy silk road: an alternative path for Pacific island countries to participate in global public health governance - Yujie Mei (BMC, 2023)
Abstract Pacific island countries (PICs) located in a region with relatively insufficient capacity to respond to public health emergencies, establishing reliable public health cooperation is conducive to maintaining security and stability. The belt and road initiative (BRI) launched by China attempts to provide a novel form of international cooperation and has supported multi-channel investment and construction. This article elucidates the history of public health cooperation between China and PICs, as well as the current situation of the BRI in the field of public health and emphasizes that there are numerous constraints in the public health cooperation between China and PICs. Given the profound impact of COVID-19 on diplomatic strategies, gradual cooperation in the field of public health may be the initial exploration of the BRI in the PICs, but it also means that the initiative must deal with challenges from geopolitical competition and cultural differences.